Sintilimab combined with axitinib in the treatment of advanced chromophobe renal cell carcinoma: a case report - Zhang, Huimin; Cong, Xiaofeng; Chen, Chen; Liu, Ziling (Frontiers in Oncology, 2024)
Chromophobe renal cell carcinoma (ChRCC) is a rare pathological type of renal cell carcinoma (RCC), related systematic studies involving large numbers of patients remain lack and more importantly, there is currently no international consensus on post-line treatment guidelines for ChRCC. The rapid development of systemic treatment with molecular targeted therapies and immune checkpoint inhibitors followed has brought effect approaches towards patients with clear cell renal cells (CCRCC) while progress in the treatment of ChRCC is still limited. In this case, the patient was initially diagnosed at early stage, 4 years post-surgery she developed lung metastases and the disease progressed once again after being treated with Sunitinib monotherapy for 3 years. However, after combining immunotherapy Sintilimab with targeted therapy Axitinib as second-line treatment, imageological examination showed lesions in lungs gradually decreased and the bone metastases remained stable. To date, the patient has been continuously treated for over 2 years and is still undergoing regular treatment and follow-up. This case is the first to report long-term survival example of metastatic disease by using this treatment regimen and propose a potential therapeutic option for patients with metastatic ChRCC. Since only one case has been observed in this report, further study is needed.